Bearsden : the story of a Roman fort - Breeze, David J. (David John) (Archaeopress Roman Sites Ser., 2016)
This accessible account of the discoveries at the Roman fort at Bearsden examines the process of archaeological excavation, the life of the soldiers at the fort based on the results of the excavation as well as material from elsewhere in the Roman Empire.